Green IT technologies and applications - Kim, Jae H. (Jae Hoon).; Lee, Myung J. (Myung Jong).; SpringerLink (Online service). (Berlin, Heidelberg Springer Berlin Heidelberg, 2011)
This book is the first of its kind in presenting comprehensive technical issues and solutions for rapidly growing Green IT. It brings together in a single volume both green communications and green computing under the theme of Green IT, and presents exciting research and developments taking place therein in a survey style. Written by the subject matter experts consisting of an international team of recognized researchers and practitioners in the field, Green IT: Technologies and Applications will serve as an excellent source of information on the latest technical trend of Green IT for graduate/undergraduate students, researchers, engineers, and engineering managers in the IT (Electrical, Communications, Computer Engineering, Computer Science, Information Science) as well as interdisciplinary areas such as sustainability, environment, and energy. The book comprises three parts: Green Communications, Green Computing, and Smart Grid and Applications. Part I Green Communications deals with energy efficient architectures and associated performance measures in wireless communications. It covers energy issues in PHY, MAC, Routing, Application layers and their solutions for a variety of networks. Part II Green Computing deals with various energy issues in data centers, computing clusters, computing storage, and associated optimization techniques. Energy management strategies are presented to balance between energy efficiency and required qualities of services. Part III Smart Grid and Applications presents an overview and research challenges for smart grid. Applications include modeling of urban pollutant for transportation networks, Wireless Sensor Network (WSN) architecture with long range radio, and Green IT standards.
From the content: Evolving Communications Architectures: More Local is More Green -- Towards Green Wireless Communications: Metrics, Optimization and Tradeoff -- Energy-Aware Link Adaptation for a MIMO Enabled Cognitive System -- Energy Efficient MAC.
Electronic reproduction.
Keywords: Green technology; Electronic books